Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1302/0301-620x.98b6.36497
|View full text |Cite
|
Sign up to set email alerts
|

Open reduction and internal fixation of posterior malleolar fractures using the posterolateral approach

Abstract: Fixation of the posterior malleolus in trimalleolar fractures can be easily done via the posterolateral approach whereby anatomical reduction and stable fixation can be reached due to adequate visualisation of the fracture. Cite this article: Bone Joint J 2016;98-B:812-17.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 19 publications
4
61
0
1
Order By: Relevance
“…In recent years, more attention has been paid to the importance of anatomical reduction and internal fixation of PMF [23][24][25]. Anatomical reduction and fixation of posterior ankle fractures can be achieved under direct vision using a posterolateral approach, which is highly accepted [10,21,26,27]. In this study, we chose the posterolateral approach to reduce posterior ankle fractures under direct vision.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, more attention has been paid to the importance of anatomical reduction and internal fixation of PMF [23][24][25]. Anatomical reduction and fixation of posterior ankle fractures can be achieved under direct vision using a posterolateral approach, which is highly accepted [10,21,26,27]. In this study, we chose the posterolateral approach to reduce posterior ankle fractures under direct vision.…”
Section: Discussionmentioning
confidence: 99%
“…As anatomic reduction of the posterior fragment can be achieved more easily through the posterolateral approach (Verhage et al. 2016), this approach can be recommended for patients with more complicated posterior malleolar ankle fracture patterns. A recent study showed that there was no difference in functional outcome following screw or plate fixation of the posterior malleolar fragment (Erdem et al.…”
Section: Discussionmentioning
confidence: 99%
“…Abordaje posterolateral (18,19) Se realiza con el paciente en decúbito prono. La planificación preoperatoria es fundamental para decidir si se va a realizar una única incisión cutánea para abordar la fractura del peroné y la del MP, lo más frecuente, o si se va a utilizar una doble vía.…”
Section: Vía Directaunclassified